Design and Development of 89C51 Based Electrical Impedance Tomography System - Trivedi, Udayan J. (My University, 2013)
Electrical Impedance Tomography is an imaging technique used in Medical, Industrial and Geophysical fields for imaging the interior parts of human body, process control, looking beneath the earth respectively. The subject of this dissertation is the design of the Data Acquisition electronics for use in a medical imaging system based on Electrical Impedance Tomography (EIT). And make the software to reconstruct the conductivity distribution image. The data is required to be sufficiently accurate to allow the successful image of absolute conductivity. In this dissertation work the EIT system is Designed and developed around Microcontroller 89C51 and op-amp based constant current source. The data acquisition system and the image reconstruction program were developed on VB.10 and EIDORS tool kit for MATLAB R2011a. The system was tested on the 2D phantom to see the ability of the system to reconstruct the 2D image of the phantom. The different imaging algorithms are implemented and compared to reconstruct the image. The developed system can be used as a prototype in the laboratory for the evaluation of EIT technique.
Master of Engineering
Keywords: ELECTRICAL IMPEDANCE TOMOGRAPHY; Microcontroller 89C51